Characterization of limb differences in children with Cornelia de Lange Syndrome. Issue 2 (27th April 2016) - Mehta, Devanshi; Vergano, Samantha A. Schrier; Deardorff, Matthew; Aggarwal, Sarika; Barot, Akash; Johnson, Drew M.; Miller, Nathan F.; Noon, Sarah E.; Kaur, Maninder; Jackson, Laird; Krantz, Ian D.
Abstract : Cornelia de Lange syndrome (CdLS) is a well‐described multisystem developmental disorder characterized by dysmorphic facial features, growth and behavioral deficits, and cardiac, gastrointestinal, and limb anomalies. The limb defects seen in CdLS can be mild, with small feet or hands only, or can be severe, with variable deficiency defects involving primarily the ulnar structures and ranging from mild hypoplasia of the fifth digit to complete absence of the forearm. Interestingly, the upper limbs are typically much more involved than the lower extremities that generally manifest with small feet and 2–3 syndactyly of the toes and shortened fourth metatarsal. The upper limbs often manifest asymmetric involvement. The limb findings in our cohort of 378 individuals with CdLS demonstrate a consistent pattern of laterality and symmetry involvement (with increased severity of right‐sided limb in individuals with asymmetric limb defects) and a correlation of more significant limb defects with an increased risk of other structural anomalies, and more severe behavioral outcomes. Additionally, we found that individuals with mutations in NIPBL were most likely to have limb defects compared to mutations in other genes with nonsense, exonic deletion, and frameshift mutations being most prevalent in those with limb defects. Characterization of the limb differences in children with CdLS may provide a tool to assist in genetic counseling and determining prognosis. This paper will review the limb involvement in a large cohort of individuals with CdLS assessing the correlation with molecular etiologies, symmetry, additional structural birth defects, and cognitive outcomes. © 2016 Wiley Periodicals, Inc.